Neuroplasticity in Depressed Individuals Compared with Healthy Controls - Player, Michael J (Nature Publishing Group, 2013)
Several lines of evidence suggest that neuroplasticity is impaired in depression. This study aimed to compare neuroplasticity in 23 subjects with DSM-IV major depressive episode and 23 age- and gender-matched healthy controls, using an objective test that is independent of subject effort and motivation. Neuroplasticity was assessed in the motor cortex using a brain stimulation paradigm known as paired associative stimulation (PAS), which induces transient changes in motor cortical function. Motor cortical excitability was assessed before and after PAS using single-pulse transcranial magnetic stimulation (TMS) to induce motor evoked potentials (MEPs) in a hand muscle. After PAS, MEP amplitudes significantly increased in healthy controls compared with depressed subjects (P=0.002). The functional significance of motor cortical changes was assessed using a motor learning task—a computerized version of the rotor pursuit task. Healthy controls also performed better on motor learning (P=0.02). BDNF blood levels and genotype were assayed to determine any relationship with motor cortical plasticity. However, PAS results did not correlate with motor learning, nor appear to be related to BDNF measures. The significance of these findings is that it provides one of the first direct demonstrations of reduced neuroplasticity in depressed subjects, using an objective test.